Nanotechnology- future prospect in recent medicine: a review - Jena, Monalisa; Mishra, Swati; Jena, Swetalina; Mishra, Sudhanshu S. (International Journal of Basic & Clinical Pharmacology, 2017)
Any damage at molecular or cellular level is the major culprit for disease & ill health. Nanotechnology, “the manufacturing technology of the 21st century," helps us economically build a broad range of complex molecular machines by manipulating matter on an atomic and molecular scale. Nanotech may be able to create many new materials and devices with at least one dimension sized from 1 to 100 nanometres with a vast range of applications, such as in medicine, electronics, biomaterials and energy production. Lots of new possibilities come into account in relation to use of nanotechnology in medicines. Nanotechnology in medicine involves applications of nanoparticles, also involves nano-robots to make repairs at the cellular levels. On the other hand, nanotechnology raises many of the same issues as any new technology, including concerns about the toxicity and environmental impact of nanomaterials.